Effect of nursery raising practices of seedlings and phosphatic fertilizer management in tomato (Solanum lycopersicum) crop on growth and yield - KOTUR, S C (The Indian Journal of Agricultural Sciences, 2014)
The raised bed seedlings produced significantly higher fruit yield of 20.4% (71.147 tonnes/ha) than the tomato grown from pro-tray seedlings (59.361 tonnes/ha). Banding of superphosphate along with other fertilizers at 5cm depth showed significantly higher yield, dry matter production, P content as well as P uptake. The fruit yield and dry matter obtained were the highest at 80% recommended P dose. In the tomato grown from raised bed seedlings, 82.706 tonnes/ ha fruit yield was obtained that was 49.3% higher than 55.383 tonnes/ha of tomato grown from pro-tray seedlings when 80% P dose was banded at 5cm depth.